Emelin - Randall, Jackie (Rouse Hill, NSW : Schillings, 2017)
"Emelin Lambert is an eleven-year-old orphan in medieval England. Who has an incredible gift in illuminating manuscripts. She's also quick-witted, mouthy, and nearly always in trouble. One terrible day, her last relative is killed and Emelin ends up being in possession of a manuscript that belongs to Geoffrey Chaucer. She cannot stay safely in her home with the manuscript so she begins a grim wintery journey to what she hopes will be safety. Along the way Emelin meets a boy named Wolf who rescues her from a violent thief. Together, Wolf and Emelin flee to Reading Abbey. The journey makes Wolf deathly ill and Emelin learns that she cannot always depend on others. She will have to fight alone, so she battles the adult world, and she battles fear. She puts her gift to work with the hope that her skills might help her and Wolf survive."--Back cover.
Keywords: Homeless teenagers -- Juvenile fiction; Historical fiction, English -- England -- Juvenile fiction; Australian